Phylogenomics as an effective approach to untangle cross-species hybridization event: A case study in the family Nymphaeaceae - Cheng, Lin; Han, Qunwei; Chen, Fei; Li, Mengge; Balbuena, Tiago Santana; Zhao, Yiyong (Frontiers in Genetics, 2022)
Hybridization is common and considered as an important evolutionary force to increase intraspecific genetic diversity. Detecting hybridization events is crucial for understanding the evolutionary history of species and further improving molecular breeding. The studies on identifying hybridization events through the phylogenomic approach are still limited. We proposed the conception and method of identifying allopolyploidy events by phylogenomics. The reconciliation and summary of nuclear multi-labeled gene family trees were adopted to untangle hybridization events from next-generation data in our novel phylogenomic approach. Given horticulturalists' relatively clear cultivated crossbreeding history, the water lily family is a suitable case for examining recent allopolyploidy events. Here, we reconstructed and confirmed the well-resolved nuclear phylogeny for the Nymphaeales family in the context of geological time as a framework for identifying hybridization signals. We successfully identified two possible allopolyploidy events with the parental lineages for the hybrids in the family Nymphaeaceae based on summarization from multi-labeled gene family trees of Nymphaeales. The lineages where species Nymphaea colorata and Nymphaea caerulea are located may be the progenitors of horticultural cultivated species Nymphaea 'midnight' and Nymphaea 'Woods blue goddess'. The proposed hybridization hypothesis is also supported by horticultural breeding records. Our methodology can be widely applied to identify hybridization events and theoretically facilitate the genome breeding design of hybrid plants.